Development of innovative analytical tools for the monitoring of Vibrio populations in aquatic environments - Silva, Elise Da (CCSD, 2017)
Mass mortality events affecting the Pacific oyster Crassostreae gigas on French coasts since 2008 have been associated to some Vibrio species. These mortalities, particularly severe and sudden in the mediterranean lagoons, can reach 80 to 100% of the oyster production threatening the sustainability of this activity. An environmental monitoring of these bacteria appears essential and, for this purpose, innovative analytical methods have to be developed as alternative to classical techniques, in order to allow the rapid and in real time monitoring of Vibrio in the coastal aquatic environments. In this context, the objective of the thesis was to design genosensors as analytical tools for Vibrio detection and quantification in aquatic ecosystems. In a first step, a system based on a « sandwich » hybridization format, in which nucleic acid targets were bound between an immobilized capture probe and a labeled signal probe, coupled with an optical detection method, was developed. After experimental condition optimization, the test showed high sensitivity with a limit of detection of 5 ng.µL-1 of nucleic acids and was highly specific to Vibrio spp. The method was then successfully applied to Vibrio detection in environmental samples collected in Salses-Leucate lagoon. A second hybridization format, based on a competition between the targeted nucleic acids and the capture probe for the signal probe has been considered using both optical and electrochemical transductions. Concurrently with the development of genosensors, quantitative real-time PCR have been designed as reference methods. Les épisodes de mortalité massive de l’huître creuse Crassostreae gigas observés sur les côtes françaises depuis 2008 ont été associés à certaines espèces appartenant au genre bactérien Vibrio. Ces mortalités, particulièrement intenses et rapides au cœur des lagunes méditerranéennes, atteignent 80 à 100% de la production ostréicole remettant ainsi en cause la pérennité de cette activité. Une surveillance environnementale de ces ...